2012
DOI: 10.1038/oby.2011.151
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Nongenetic Variability in Body Weight Gain Induced by a High‐Fat Diet in Inbred C57BL/6J Mice

Abstract: Inbred C57BL/6J mice displayed large individual variations in weight gain when fed a high‐fat diet (HFD). The objective of this study was to examine whether this predominantly nongenetic variability could be predicted by relevant baseline features and to explore whether variations in these significant features were influenced during pregnancy and/or lactation. Fat mass (FM), fat‐free mass (FFM), food intake (FI), resting metabolic rate (RMR), physical activity (PA), and body temperature (Tb) were all evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 43 publications
6
35
1
Order By: Relevance
“…Approximately 12% of the variation in BM and 11% of the variation in FM could be predicted by sex and FFM; animals that had a higher FFM before the diet intervention showed greater HFD-induced weight gain. These results agree with a previous study in inbred male C57BL/6 mice that found FFM to be a significant predictor of HFD-induced weight gain [55]. In that study, FM and physical activity were also shown to significantly contribute to the models, which is in agreement with a study using genetically obese ob/ob mice, which displayed reduced activity levels before the onset of obesity at the time when they were the same BM as their lean littermates [7].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Approximately 12% of the variation in BM and 11% of the variation in FM could be predicted by sex and FFM; animals that had a higher FFM before the diet intervention showed greater HFD-induced weight gain. These results agree with a previous study in inbred male C57BL/6 mice that found FFM to be a significant predictor of HFD-induced weight gain [55]. In that study, FM and physical activity were also shown to significantly contribute to the models, which is in agreement with a study using genetically obese ob/ob mice, which displayed reduced activity levels before the onset of obesity at the time when they were the same BM as their lean littermates [7].…”
Section: Discussionsupporting
confidence: 93%
“…Studying this individual variability in responses could reveal processes of individual weight regulation and establish the biological factors that make people either susceptible or resistant to weight gain, which is crucial to increase our understanding of the aetiology of obesity. For example, in male Sprague Dawley rats on pure macronutrient or high fat diets, measures of weight gain, energy intake or fat preference are shown to vary considerably in direct proportion to ultimate body fat gain ( [28,39,49], also see [55] in mice).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with studies on birds, the evidence with respect to stochastic variations in food supply are less clear cut compared with the impacts of modified predation risk. There is some limited support for the idea that increased stochasticity drives elevated fat storage Cao et al, 2009;Zhang et al, 2012;Zhu et al, 2014); however, other studies suggest the reverse (Monarca et al, 2015b). In humans, this idea is generally called the 'food insecurity' hypothesis, or the 'hunger-obesity' paradigm (Nettle et al, 2017;Dhurandhar, 2016), i.e.…”
Section: Set-point Theorymentioning
confidence: 97%